CRIME SCIENCE : METHODS OF FORENSIC DETECTION - JOE NICKELL, JOHN F. FISCHER (University Press of Kentucky, 2013)
The rational basis upon which the work of today's investigator is predicated is called the scientific method. This method is empirical (from the Latin empiricus, "experienced"), meaning that knowledge is gained from direct observation. Underlying the empirical attitude is a belief that there is a real knowable world that operates according to fixed rules and that effects do not occur without causes.1 In contrast to, say, religious dogma, science is open-ended: It is amenable to being amplified or to having its errors corrected in the light of new evidence. For our purposes, the scientific method is one that involves analysis (studying the unknown item to determine its essential characteristics), comparison (examining how the characteristics compare with the established properties of known items), and evaluation (assessing the similarities and dissimilarities for identification purposes) ? Forensic means characteristic of, or suitable for, a court of law. Hence forensic science is a broad term that embraces all of the scientific disciplines that are utilized in investigations with the goal of bringing criminals to justice. The American Academy of Forensic Sciences defines it as "the study and practice of the application of science to the purposes of the law."3 It includes such fields as forensic medicine, toxicology, psychology, and anthropology as well as the work of specialized examiners of fingerprints, firearms, tool marks, and questioned documents. The term is so broad as to include even criminology, a social science that plays a role in the administration of civil law. Like criminology, criminalistics is a division of forensic science, and its practitioner is called a "criminalist." The discipline has been variously defined. In 1963, the California Association of Criminalistics adopted the following definition: "Criminalistics is that profession and scientific discipline directed to the recognition, identification, individualization and evaluation of physical evidence by application of the natural sciences to law-science matters."4 This definition has since been adopted by the American Academy of Forensic Sciences.